The Implementation of Social Protection Policy on Health Insurance for the Poor - Muhtar Muhtar (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2015)
Verification and validation data that produce valid data, that become the entry point on accessibilities of proper health services for the poor haven’t been made by the socia institutions. This study aims to present information the implementation of social protection policy of health insurance for the poor: the verification and validation of data, that taking Jambi municipality as a case study. By using qualitative descriptive method, this study showed that social protection policy on health insurance has yet maximized covering poor people in the municipality of Jambi, because it hasn’t been verified and validated the data, as a result of social protection policy that haven’t been communicated by the health carecenter management to the regions.